Paleoceanography and ice sheet variability offshore Wilkes Land, Antarctica. Part 2; Insights from Oligocene-Milocene dinoflagellate cyst assemblages: - Bijl, P.K.; Houben, A.J.P.; Hartman, J.D.; Pross, J.; Salabarnada, A.; Escutia, C.; Sangiorgi, F. (2018)
Next to atmospheric CO2 concentrations, iceproximal oceanographic conditions are a critical factor for